Frailty and Sarcopenia Recent Evidence and New Perspectives - D'Onofrio, Grazia; Cseri, Julianna (IntechOpen, 2022)
Sarcopenia is a symptom of aging that contributes to the functional decline of the musculoskeletal system, responsible for impaired gait and balance and a high risk of falls and serious fractures. Nutrition and exercise play a key role in the prevention and treatment of sarcopenia. Due to the multifaceted nature of sarcopenia, the best therapeutic approach is multidisciplinary, requiring collaboration between specialists such as geriatricians, internists, physiatrists, general practitioners, nutritionists, and physiotherapists. This book presents a comprehensive overview of sarcopenia with chapters on physiopathological mechanisms, assessment tools, and rehabilitation activities of the condition in the frail elderly.